DAMPAK PRENATAL BREAST CARE PADA KEHAMILAN TRIMESTER III TERHADAP PRODUKSI DAN KELANCARAN PENGELUARAN ASI IBU POST PARTUM - Kotarumalos, Sitti Sarifah; Wetir, Erina; Mayano, Kesya A. (Poltekkes Kemenkes Maluku, 2024)
Prenatal breast care in the third trimester of pregnancy has a positive impact on the frequency of breast milk production in the postpartum period, supporting the success of exclusive breastfeeding programs. Midwives play a key role in providing prenatal breast care and education to pregnant women to enhance breastfeeding success. Further research on the benefits of prenatal breast care can provide a strong scientific basis for clinical practice and health policies that support exclusive breastfeeding programs. This study was an experimental type of research with a Pre-experimental design. The research method used a case study approach by providing comprehensive midwifery care to mothers starting in the third trimester of pregnancy and postpartum visits with the goal of prenatal breast care in the third trimester of pregnancy impacting production and smoothness of postpartum breast milk release. The research results showed that prenatal breast care applied during pregnancy, especially in the third trimester, had an impact on postpartum breast milk production and smoothness.